Pelaksanaan Menebar Kebahagiaan untuk Anak Yatim dan Piatu: Studi Pengabdian Masyarakat di Pondok Pesantren Bening Hati Sawangan - Idrus, Ali; Fahriah, Putri Haezah; Gusnawan, Agung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research departs from the concern about the emotional and social conditions of orphans who often experience a lack of attention and affection after losing their parents. The purpose of this study is to evaluate the effectiveness of the spreading happiness program in improving the emotional and social well-being of orphans at the Sawangan Islamic Boarding School. This research also identifies the factors that influence the success of the program as well as the obstacles faced in its implementation. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results showed that this program has a positive impact on the welfare of children, although there are still some obstacles that need to be overcome. This research provides recommendations for future program improvements.